Efficient phosphate removal from water using ductile cast iron waste: a response surface methodology approach - Roushdy, Mai Hassan; Elkhashab, Nada Amr; Osman, Ahmed Ibrahim; Ali, Dalia Amer (Frontiers in Chemistry, 2024)
Water scarcity is a critical issue worldwide. This study explores a novel method for addressing this issue by using ductile cast iron (DCI) solid waste as an adsorbent for phosphate ions, supporting the circular economy in water remediation. The pseudo-second-order (PSO) kinetics model and Langmuir isotherm were fitted with the experimental results with maximum adsorption capacity (qmax = 0.28 mg/g). The thermodynamic analysis indicated that this adsorption process was spontaneous based on the negative value of Gibbs free energy (∆G). Additionally, the positive values of enthalpy (∆H) indicated the endothermic nature of this adsorption system. It was able to reach the highest adsorption percentage of 98.9 (%) for phosphate ions from aqueous solutions using response surface methodology (RSM) with optimum conditions of 10 mg/L phosphate ion concentration, pH = 8, normal room temperature, 9 min adsorption, and 0.5 g/L adsorbent dosage.